Benefits of probiotics in preterm neonates in low-income and medium-income countries: a systematic review of randomised controlled trials. Issue 12 (7th December 2017) - Deshpande, Girish; Jape, Gayatri; Rao, Shripada; Patole, Sanjay
Abstract : Objective: Although there is an overall reduction in underfive mortality rate, the progress in reducing neonatal mortality rate has been very slow. Over the last 20 years, preterm births have steadily increased in low-income and medium-income countries (LMICs) particularly in sub-Saharan Africa and South Asia. Preterm birth is associated with increased mortality and morbidity, particularly in LMICs. Based on systematic reviews of randomised controlled trials (RCTs), many neonatal units in high-income countries have adopted probiotics as standard of care for preterm neonates. We aimed to systematically review the safety and efficacy of probiotics in reducing mortality and morbidity in preterm neonates in LMICs. Design: Systematic review and meta-analysis of RCTs. Data sources: Medline, Embase, Cochrane Central Register of Controlled Trials, Cumulative Index of Nursing and Allied Health Literature and E-abstracts from Pediatric Academic Society meetings and other paediatric and neonatal conference proceedings were searched in January 2017. Eligibility criteria: RCTs comparing probiotics versus placebo/no probiotic in preterm neonates (gestation<37 weeks) conducted in LMICs. Results: Total 23 (n=4783) RCTs from 4 continents and 10 LMICs were eligible for inclusion in the meta-analysis using fixed effect model. The risk of necrotising enterocolitis (NEC greater than or equal to stage II) (risk ratio (RR) 0.46 (95% CI 0.34 to 0.61), P<0.00001, numbers needed to treat (NNT) 25 (95% CI 20 to 50)), late-onset sepsis (LOS) (RR 0.80 (95% CI 0.71 to 0.91), P=0.0009, NNT 25 (95% CI 17 to 100)) and all-cause mortality (RR 0.73 (95% CI 0.59 to 0.90), P=0.003, NNT 50 (95% CI 25 to 100)) were significantly lower in probiotic supplemented neonates. The results were significant on random effects model analysis and after excluding studies with high risk of bias. No significant adverse effects were reported. Conclusion: Probiotics have significant potential to reduce mortality and morbidity (eg, NEC, LOS) in preterm neonates in LMICs.